Manpower Scheduling with Time Windows - LIM, Andrew (Institutional Knowledge at Singapore Management University, 2003)
In this paper, we propose a manpower allocation model with time windows which is of practical interest to serviceman scheduling operations. Specifically, this problem originates from peculiar port yard scheduling needs where demand is generated from locations in the yard for servicemen who are dispatched from a central point and where the objectives are to minimize the number of servicemen scheduled, travel distances, travel times and waiting times at each location. Although closely related to the well-known vehicle routing problem, this problem is different while its solution could provide insight to the latter. We develop solutions using metaheuristic methods, and in particular provide tabu embedded simulated annealing and squeaky wheel optimization with local search algorithms for this problem. We apply these newly-developed metaheuristics with adaptations for solutions to the manpower allocation problem, while our analysis throws light on how these work. Computational results are reported which show the effectiveness of our approach when applied to the manpower allocation problem.